Second Report on the Publication and Conservation of the Tomb of Ramesses III in the Valley of the Kings (KV 11) - Weber, Anke.
The Ramesses III (KV 11) Publication and Conservation Project is currently developing a site management, conservation and publication strategy for the severely damaged tomb of pharaoh Ramesses III in order to prevent further deterioration and to preserve this cultural heritage site for future generations. Along with first urgent measures of conservation, a geo-archaeological survey of KV 11 and its surroundings, as well as a geomatic and photogrammetric survey of the tomb itself, were carried out. The detailed recording of the current state of the architecture and wall decoration allowed for further reconstruction of scenes and texts. Moreover, an archaeological sondage in the burial chamber revealed additional information about the ooding and sedimentation processes. A field school with students of Luxor University offered training in digital recording methods and epigraphy, geo-archaeological survey and mapping methodologies, and conservation treatment and assessment. The following article outlines preliminary results in the fields of geology, conservation, recording, reconstruction, and excavation. doi: http://dx.doi.org/10.5913/jarce.56.2020.a014